Modification of a vaccine hesitancy scale for use in adult vaccinations in the United States and China. Issue 8 (3rd August 2021) - Akel, Kaitlyn B.; Masters, Nina B.; Shih, Shu-Fang; Lu, Yihan; Wagner, Abram L.
ABSTRACT: Most research on vaccine hesitancy has focused on parental attitudes toward childhood vaccination, but it will be important to understand dimensions of vaccine hesitancy in the adult population as more adult vaccines are introduced in the future. We modified the Vaccine Hesitancy Scale to target adult vaccines and provide measures of its reliability and validity relative to influenza vaccine uptake and COVID-19 vaccination acceptance in cross-sectional internet surveys in the United States and in China. We assessed the impact of vaccine hesitancy on influenza and COVID-19 vaccination using multivariable regression modeling, which informed concurrent validity of the adult Vaccine Hesitancy Scale (aVHS). Among 1103 participants in the March 2020 China survey, 5.4% would not accept a COVID-19 vaccine, whereas this figure was 18.8% for the March 2020 US survey and 27.3% for the June 2020 US survey. The aVHS exhibits good internal consistency in all three surveys. Models adjusted for age, gender and income level show that prevalence of COVID-19 vaccine acceptance was a fraction as high in those who scored higher on the VHS than those who scored lower on all three surveys. Prevalence of past and future flu vaccine acceptance was a fraction as high in those with higher aVHS scores than those with lower scores. Prevalence of COVID-19 vaccine acceptance is lower in those with higher vaccine hesitancy scores, which supports the scale's concurrent validity. The aVHS exhibits good internal consistency, making it a valid and reliable tool for measuring vaccination uptake.